Behavioural intention with respect to unit trust investment decision: the influence of perceived utilitarian and hedonic product benefits - Wan Nawang, Wan Rasyidah (2020)
This study purports to empirically investigate the influence of utilitarian and hedonic benefits on behavioural intention with regards to unit trust investment within the Malaysian context. This study builds on previous works on utilitarian versus hedonic considerations. Due to the study exploratory nature, a mixed method methodology that combins both qualitative and quantitative techniques was employed. The qualitative approach utilises a semi-structured interview involving 16 working individuals was conducted. The major aim of qualitative study is to explore the key product attributes/features for unit trust and the individual’s value expectation from those features. The respondents mentioned that the key product features that they look for in choosing and deciding to purchase unit trust are brand recognition, service quality, financial advice, financial return, fund types, overall fund manager reputation, whether the fund is legal or not, and the fund liquidity. It is surprising that financial return is not the first key product feature that most of the respondents consider while making investment choice and decision. This was followed by quantitative work using experimental design study. The main objective of quantitative work is to examine the causal effect of unit trust product features, choice decision, value expectation, and behavioural intention. The experimental design in the second part of the study involves fictitious unit trust provider, in which respondents were allocated to one of six treatment groups with different product types (conventional and Islamic unit trust) and product features (utilitarian dominant vs. hedonic dominant vs. equally utilitarian and hedonic). The survey was participated by 569 respondents, involving undergraduates from business faculty of public universities. This study expects to find variation in the perceived utilitarian and hedonic pertaining to unit trust investment. no differences were recorded. Neverthless, the results from qualitative study did provide evidence that unit trust investment contains both utilitarian and hedonic elements, and both elements deliver some values to be considered when purchasing unit trust funds. Given that Malaysia is a multi-cultural nation, the findings of the study suggest that culture and religion had some effect on individuals’ fund decision. Therefore, fund management companies might make use of the information provided by this study in better promoting their funds.